INTERACTIVE METHODS AS A CONDITION FOR INTERACTIVE EDUCATION - Alimova Nozima Rajabboevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The goal of personality development required the search and selection of methods that actively influence the formation of students’ personal qualities. Interactive methods have the potential for intense motivation, which greatly contributes to the personal development of students at all levels of the education system. Training and development are perennial pedagogical problems. At different stages of human society, even in different ethnic communities and social groups, this problem was periodically actualized, tried to be solved and solved in different ways.